Measuring the influence of perceived organizational support, organizational hierarchy culture, strategic human resource management, and psychological empowerment on the return to work - Tawfig, Nadra; Farsi, Suhad; Lary, Alaa; Aggad, Kholod (Frontiers in Rehabilitation Sciences, 2026)
In this era of high competition and pandemic, the return to work is challenging because it requires organizations to balance operational demands with individualized support for employees recovering from psychological, physical, and/or personal setbacks. Additionally, managerial expectations, misalignment between workplace culture, and employee readiness can hinder effective reintegration, leading to reduced relapse or productivity. This study aimed to examine the influence of key organizational and psychological factors on employees' return-to-work. A stratified sampling approach was employed to collect data from 370 employees who had successfully returned to work after experiencing work-related injuries and diseases. Eight hypotheses were formulated and validated using structural equation modeling with SmartPLS. Findings from the present study reveal that perceived organizational support has an insignificant impact on the return to work; however, it has a significant impact on strategic human resource management and psychological empowerment. In addition, the present study confirmed a significant impact of organizational hierarchy culture on return-to-work and psychological empowerment. Thus, strategic human resource management had a significant impact on return-to-work rates and psychological empowerment. Finally, psychological empowerment had a significant impact on the return to work. The study highlights the importance of culturally aligned human resource strategies and psychological factors in fostering successful employee reintegration after work absence. These findings have practical implications for human resource professionals and policymakers aiming to design effective, inclusive, and sustainable return-to-work programs tailored to hierarchical organizational environments.